Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.burns.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied metal chelator reduces thermal injury progression in a rat model of brass comb burn

Abstract: Oxidative stress may be involved in the cellular damage and tissue destruction as burn wounds continues to progress after abatement of the initial insult. Since iron and calcium ions play key roles in oxidative stress, this study tested whether topical application of Livionex formulation (LF) lotion, that contains disodium EDTA as a metal chelator and methyl sulfonyl methane (MSM) as a permeability enhancer, would prevent or reduce burn injury. Methods We used an established brass comb burn model with some mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…For instance, topical EDTA-MSM is effective at reducing oxidative damage in the form of protein-lipid aldehyde adducts [170,171,172]. EDTA-MSM reduced lens opacification in diabetic cataract [172] but was ineffective in reversing experimentally induced intraocular pressure in rats [170].…”
Section: Common Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, topical EDTA-MSM is effective at reducing oxidative damage in the form of protein-lipid aldehyde adducts [170,171,172]. EDTA-MSM reduced lens opacification in diabetic cataract [172] but was ineffective in reversing experimentally induced intraocular pressure in rats [170].…”
Section: Common Usesmentioning
confidence: 99%
“…Another final study report indicated that MSM may be slightly irritating to skin of guinea pigs. Using a lotion containing EDTA and MSM, mild improvement in burn sites on rats were noticed following three days of topical application every 8 h [171]. …”
Section: Common Usesmentioning
confidence: 99%
“…Lessening the impact of the extensive scarring that affects 70–90% of severely burned patients has become a research priority, prompting the development of reliable animal models to study post-burn wound healing and hypertrophic scarring (15, 18, 91, 92) to parallel studies of the patients themselves.…”
Section: Post-burn Hypertrophic Scarringmentioning
confidence: 99%
“…While collagen, necessary for chondrocytes and osteoblasts, can promote the adhesion and migration of bone cells, the formation of collagen matrix, and the reconstruction of bone tissue[10, 11]. However, MSM is easily metabolized and excreted, which lead to short duration of efficacy[12-14].…”
Section: Introductionmentioning
confidence: 99%